WISATA RELIGI, NGINTUN SANTRI DALAM MENINGKATKAN EKONOMI SEKITAR PESANTREN - Nafisah, Siti Dwi; Syarofi, Muhammad (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2025)
This research explores the potential of religious tourism in the “Ngintun Santri” tradition around pesantren, focusing on its impact on the local economy. The tradition of sending santri to pesantren not only has spiritual and social dimensions, but also makes a significant economic contribution to street vendors and the surrounding community. The purpose of this study is to analyze the potential of religious tourism “Ngintun Santri” in improving the economy of street vendors around the pesantren, contributing to the strengthening of the local economy, and formulating a sustainable religious tourism development strategy. The research method used was a qualitative approach with a case study, involving in-depth interviews and direct observation. Data analysis was conducted using the Miles and Huberman method, including data collection, data reduction, data presentation, and conclusion drawing. The novelty of this research lies in combining the concept of religious tourism with the local culture of pesantren, specifically “Ngintun Santri”, as a new approach to identify the economic potential of specific and unique religious traditions. The results show that the tradition of “Ngintun Santri” has a significant impact on improving the local economy